FORMATION OF THE STATE POLICY IN PUBLIC HEALTHCARE IN THE RUSSIAN FEDERATION: PROBLEMS AND SOLUTIONS - A.A. Baranov; Yu.E. Lapin (Вопросы современной педиатрии, 2006)
The article analyzes the legal grounds for the state policy development in public healthcare in the Russian federation. The urgency of this program is well substantiated. The authors introduce the working definition of the governmental policy in public healthcare, which is viewed as a component of the internal policy of the state and which interacts with other trends of the state policy within the framework of its tasks. The adequate state regulation of the legal, social and economic and other relations within the society is necessary to achieve maximum full observance of the citizens' rights for the disease prevention, affordable highly qualified medical care and medical rehabilitation.Key words: public healthcare, medical care.